2019
DOI: 10.32479/ijefi.8327
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Market Openness on Economic Growth for Poland: An Autoregressive Distributed Lag Bounds Testing Approach to Cointegration

Abstract: The aim of this paper is to analyze the relationship between international trade, economic and financial development for Poland during the period 1990-2016. For the analysis of this relationship we apply the autoregressive distributed lag (ARDL) technique and the error correction model (ECM) as it was formed by Pesaran and Shin (1999) and Pesaran et al. (2001), as well as the augmented Cobb-Douglas production function formed by Mankiw et al. (1992). The results of ARDL test and ECM confirm the existence of lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…Similarly, it was found that private consumption (PRC) had a positive relationship with economic performance across all quantiles. This result was in agreement with the findings of Guo and N’Diaye (2010), Nikbin and Panahi (2016), Damane (2018) and Pegkas, (2018). For instance, Damane (2018) suggested that growth in GDP leads to an increase in household income and, therefore, a rise in the level of private consumption over time.…”
Section: Empirical Findingssupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, it was found that private consumption (PRC) had a positive relationship with economic performance across all quantiles. This result was in agreement with the findings of Guo and N’Diaye (2010), Nikbin and Panahi (2016), Damane (2018) and Pegkas, (2018). For instance, Damane (2018) suggested that growth in GDP leads to an increase in household income and, therefore, a rise in the level of private consumption over time.…”
Section: Empirical Findingssupporting
confidence: 93%
“…This was consistent with the findings of previous studies that an increase in public consumption is harmful to a country (Afonso & Jalles, 2016; Khan et al, 2020), and the finding of the adverse effect of debt on economics is consistent with Shclarek (2004), Kumar and Woo (2010), Pegkas (2018), Sani et al (2019) and Law et al (2021). On the other hand, investment, population, private consumption, institutional quality and trade openness positively influenced economic growth when the country had a low economic growth, and these findings are in line with Guo and N’Diaye (2010), Nikbin and Panahi (2016), Damane (2018) and Pegkas (2018), who found that private consumption promotes economic growth; scholars Khan et al (2018) and Awan and Qasim (2020) support the view that investment stimulates economic growth. Besides that, the positive sign of population is consistent with the findings of Furuoka (2013) and the same for institutional quality, which is also supported by Hasan et al (2009).…”
Section: Empirical Findingssupporting
confidence: 79%
“…Using different estimation methods in various countries, a number of empirical works added openness in trade to the production function to study its effect on economic growth (Miller and Upadhyay, 2000) for the developed and developing countries; Yeboah et al (2012) for African countries; and Dritsaki and Stamatiou (2019) for Poland). Only Dritsaki and Stamatiou (2019) found that trade openness is insignificant to economic development both in the short and long run, while the other studies concluded that trade openness promotes economic growth. Therefore, we choose to use the Cobb-Douglas type production function:…”
Section: Econometric Methodsmentioning
confidence: 98%
“…On Table 1, the results obtained for the unit root test using the Dickey-Fuller and Phillip and Perron procedures are shown. The results show that the variables are stationary and integrated in the first difference I(1), which is, a priori, a requirement for an ARDL estimation (Greaves, 2018). For analysis purposes, the data from each series were changed into logarithms to reduce the variance and facilitate its interpretation in terms of elasticity.…”
Section: Unit Root Lags Number and Cointegrationmentioning
confidence: 99%